Monitoring, endogenous comparative advantage, and immigration - Dhimitri Qirjo (IZA Journal of Migration, 2015)
We propose a theory of free movement of goods and labor between two economies in the presence of moral hazard. Each country produces two final goods where the productive efforts of workers cannot be perfectly observed, or verified only in the complex industry. We show that national institutional quality and the system of the early childhood care and education determine the pattern of international trade. However, individuals' decisions to emigrate depend only on the national institutional quality, where the country with more developed institutions serves as the host country of immigrants. We conclude that international labor movement promotes international trade.
Keywords: B52; I21; F10; F16; F22; J24; 330; Comparative advantage; Occupational choice; Education; Institutions; Immigration; Moral hazard; Organization of production close